The Impact of Monetary Policy on the Brazilian Stock Market - Melo, Marcelo Miranda; Gomes, José Weligton Félix (Archives of Business Research, 2023)
This research used VAR/VEC methodology to explore mainly the impact of monetary policy on the Brazilian stock market. Due to persistent inflation the Brazilian Central Bank (BACEN) used high real interest rates for a long time. Recently, before COVID crisis, BACEN reduced dramatically the interest rate and provoking an outstanding performance of the Brazilian stock market. We used monthly data from January/2010 to December/2022 and the macroeconomic variables applied are described as follows: IBOVESPA Stock Market Index (IBOV), Inflation Rate (IPCA), Real Exchange Rate (EER), Economic Activity Index (IBC-Br), Interest Rate (CDI) and Intermediate Money (M2/GDP). Research results indicate that the most powerful macroeconomic variables in the Brazilian stock market are EER, CDI and M2_GDP. There is strong evidence that monetary policy affects the Brazilian stock market not only through the interest rate channel but also through an unexpected change in the monetary aggregate levels. Liquidity levels in the economy expressed by an increase of monetary aggregates tends to affect the stock market stronger than by the reduction of interest rate level.